The Power of a Small Green Place – A Case Study of Ottawa's Fletcher Wildlife Garden - Sander-Regier, Renate (Université d'Ottawa / University of Ottawa, 2013)
The Power of a Small Green Place is an ethnographic case study among the volunteers and urban wilds of Ottawa’s Fletcher Wildlife Garden (FWG). Through the conceptual lens of the geographical concept of place – with its wide range of physical, relational and deeper meaningful considerations – this urban wildlife habitat project emerged as a place of profound significance. Volunteers working to create and maintain the FWG’s diverse habitats benefit from opportunities to engage in physical outdoor activity, establish social connections, make contact with the natural world, find deep personal satisfaction and meaning, and experience healthier and mutually beneficial relations with nature. This case study fills a knowledge gap in geography regarding the significant relationships that can emerge between people and the land they work with, thereby contributing to geography’s “latest turn earthward” examining practices and relationships of cultivation with the land. The case study also contributes to a growing interdisciplinary dialogue on human-nature relations and their implications in the context of future environmental and societal uncertainties.
Keywords: place; nature; urban green space; human-nature relations; human-nature reconciliation; human-nature reciprocity; case study; ethnography; autoethnography